Medical cannabis: prescribing and research developments. (2nd July 2019) - Mendes, Aysha
Abstract : Research continues into the medicinal value of cannabis for various health conditions.Aysha Mendes provides an overview of study findings to date and explores the prospect of prescribing cannabis in future and how it may benefit patients in managing their conditions